2023
DOI: 10.1002/adma.202210732
|View full text |Cite
|
Sign up to set email alerts
|

Photostable Cascade‐Activatable Peptide Self‐Assembly on a Cancer Cell Membrane for High‐Performance Identification of Human Bladder Cancer

Abstract: Missed or residual tumor burden results in high risk for bladder cancer relapse. However, existing fluorescent probes cannot meet the clinical needs because of inevitable photobleaching properties. Performance can be improved by maintaining intensive and sustained fluorescence signals via resistance to intraoperative saline flushing and intrinsic fluorescent decay, providing surgeons with sufficiently clear and high‐contrast surgical fields, avoiding residual tumors or missed diagnosis. This study designs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Peptides have been extensively studied as building blocks due to their chemical versatility, strong biocompatibility, and predictable assembly behavior, 1,2 which could be encoded with designable sequences to fabricate biofunctional conformations directly from primary structures and allow various applications in imaging, 3–7 drug delivery 8–12 and tissue engineering. 13–16 Peptide assemblies are ordinarily governed by a combination of noncovalent and covalent interactions, encompassing hydrogen bonds, 17 π–π stacking, 18 hydrophobic interactions, 19,20 coulombic forces, 21,22 disulfide S–S bonds, 23,24 l -phenylalanine polymerization, dityrosine crosslinking, 25–27 and so on, which could drive peptide self-assembly processes, stabilize secondary or tertiary structures, and establish conjugation patterns even at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides have been extensively studied as building blocks due to their chemical versatility, strong biocompatibility, and predictable assembly behavior, 1,2 which could be encoded with designable sequences to fabricate biofunctional conformations directly from primary structures and allow various applications in imaging, 3–7 drug delivery 8–12 and tissue engineering. 13–16 Peptide assemblies are ordinarily governed by a combination of noncovalent and covalent interactions, encompassing hydrogen bonds, 17 π–π stacking, 18 hydrophobic interactions, 19,20 coulombic forces, 21,22 disulfide S–S bonds, 23,24 l -phenylalanine polymerization, dityrosine crosslinking, 25–27 and so on, which could drive peptide self-assembly processes, stabilize secondary or tertiary structures, and establish conjugation patterns even at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to targeted drug delivery, various strategies based on specific interactions between a given drug and the targeted cell have been developed. However, insufficient expression of natural receptors on the cancer cell membrane largely limits the delivery efficacy. To address this challenge, the expression of an artificial receptor, azid, on the membrane of cancer cells has been developed through metabolic glycoengineering.…”
Section: Introductionmentioning
confidence: 99%
“…The activities of peptides involve intricate mechanisms, such as supramolecular assembly, which are also crucial for peptide engineering in the development of therapeutic agents and bioimaging probes with improved performance. Sun et al discovered that self-assembling tripeptides (Phe–Phe–Tyr) effectively reverse drug resistance in melanoma by interfering with microtubules . Furthermore, the experiments demonstrated that peptide self-assembly into micelles followed by transformation into nanofibers can induce apoptosis in cancer cells by disrupting HER2 dimerization .…”
Section: Introductionmentioning
confidence: 99%